Press Coated Pulsatile Release Flurbiprofen Tablets: A Preclinical Pharmacokinetic Investigation - Reddy, Matta Nalini Krishna (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: The present study was designed to conduct a pharmacokinetic study for developed flurbiprofen press coated pulsatile release tablets (PRT), which are intended to treat early morning surge in rheumatoid arthritis. Settings and Design: A simple, accurate, specific and Linear reverse phase high-performance liquid chromatography method has been developed and validated for the estimation of Flurbiprofen in rabbit plasma. The formulated tablets were tested in vivo in New Zealand white male rabbits for various pharmacokinetic parameters. Materials and Methods: The method of estimation of flurbiprofen was developed and validated using Waters symmetry C18 (100*4.6 mm and 3.5 um) and 10 mm phosphate buffer: Acetonitrile (55:45) (pH 4.0) at 245 nm with 1.0 ml/min flow rate using Ibuprofen as an internal standard. The developed estimation method of flurbiprofen was used to conduct a pharmacokinetic study in twelve male New Zealand rabbits, which received optimized rapid release core tablets, and press coated PRT of flurbiprofen, respectively. Pharmacokinetic parameters were computed to compare the mean lag time required between administration of dosage and drug release in pulsatile formulation with that of immediate release dosage formulation. Results: The estimation method has shown repeatability and reproducibility. The extract action recoveries of Flurbiprofen were between 90% and 110%. The pharmacokinetic estimations proved the capability of press release coated tablets to achieve drug release after the desired lag time. The Cmax of press-coated tablets was 45.10 ± 9.71 μg mL−1 at Tmax of 8 h whereas it was 54.2 ± 2.18 μg/mL−1 at 2 h in case of immediate release tablets. The area under the curve for the immediate release and pulsatile release coated tablets was 356.82 μg mL−1 h−1 and 324.21 μg mL−1 h−1. Conclusion: Pulsatile tablets of flurbiprofen were successfully evaluated, which provided a desirable lag time followed by desirable drug release.